RESERVOIR CHARACTERIZATION USING PRESSURE DERIVATIVE METHOD IN NA-20 WELL SENJA FIELD - Nadhira Andini; Muh Taufiq Fathaddin; Cahaya Rosyidan (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2018)
The pressure behaviour of a well can be easily measured and is useful in analysing and predicting reservoir performance or diagnosing the condition of a well. Since a well test and subsequent pressure transient analysis is the most powerful tool available to the reservoir engineer for determining reservoir characteristics, the subject of well test analysis has attracted considerable attention. A well test is the only method available to the reservoir engineer for examining the dynamic response in the reservoir and considerable information can be gained from a well test. A well test is the examination of the transient behaviour of a porous reservoir as the result of a temporary change in production conditions performed over a relatively short period of time in comparison to the producing life of field. The build up can be both the part of the test when the well is shut in and a value represented by the difference in the pressure measured at any time during the build up and the final flowing pressure. The most common megods of transient (time dependant) pressure analysis required that data points be selected such that they fell on a well-defined straight line on either semi-logarithmic or cartesian graph paper. The well test analyst must the insure that the proper straight line has been chosen if more than one line can be drawn through the plotted data. This aspect of interpretation of well test data requires the input of reservoir engineer. Equally important is the design of a well test to ensure that the duration and format of the test is such that it produces good quality data for analysis. The results obtained from transient pressure analysis are used to discover the formation damage by detemining skin. This experiment will be analyzed oil well which is NA-20 well in Senja field. The results from the analysis of the data obtained on NA-20 well is 4.84 mD permeability, skin +1.42, pressure changes due to skin (ΔPskin) 264.384 psi, and flow efficiency 0.842 with 851.61 ft radius of investigation. The result from the analysis of the well showed that NA-20 well in Senja field have formation damage.